(untitled) (CIPEEX, 2026)
Catechins are polyphenolic flavonoids widely distributed in plant-based foods such as green tea, cocoa, grapes, and apples. Their pharmacological effects have been described in various experimental models, encompassing antioxidant, anti-inflammatory, cardioprotective, and neuroprotective properties. This study aimed to review the main scientific findings on catechins and their subgroups, with emphasis on epigallocatechin-3-gallate (EGCG) and its neuroprotective potential in neurodegenerative diseases. The study consisted of a literature review in databases such as PubMed, SciELO, and Google Scholar, covering articles published between 2015 and 2025. Original articles and relevant narrative reviews were included. The results show that catechin exhibits important anti-inflammatory effects by reducing pro-inflammatory mediators (COX-2, TNF-α, NF-κB); epicatechin, abundant in cocoa, improves endothelial function by increasing nitric oxide bioavailability; proanthocyanidins from grape seeds display cardioprotective effects against drug-induced toxicity; and EGCG, the main catechin in green tea, exerts a potent neuroprotective effect by inhibiting the aggregation of TDP-43 protein associated with amyotrophic lateral sclerosis. In conclusion, catechins stand out as promising bioactive compounds, with EGCG being the most studied derivative in the context of neurodegenerative diseases.